2011
DOI: 10.1016/j.carbon.2010.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer graphene grown by precipitation upon cooling of nickel on diamond

Abstract: Multilayer graphene is grown by precipitation upon cooling of a thin nickel film deposited by e-beam evaporation on single crystal diamond (001) oriented substrates. Nickel acts as a strong catalyst inducing the dissolution of carbon from diamond into the metal. Carbon segregation produces multilayers of graphene on the top surface. Characterization by Raman spectroscopy reveals that these thin layers display relatively narrow Raman phonon peaks that are typically associated with graphene. Atomic force microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 36 publications
4
45
0
Order By: Relevance
“…This result can be understood based on a very low solubility of carbon on copper [29]. It has been reported that the catalyst is closely related to the growth of multilayer graphene by PUC on diamond [30]. Consequently, an extended PUC growth mechanism for GNW is proposed to interpret the growth GNWs on the diamond substrate that matches the experiment results very well.…”
Section: The Growth Mechanism Of Gnws Grown On Diamondsupporting
confidence: 65%
“…This result can be understood based on a very low solubility of carbon on copper [29]. It has been reported that the catalyst is closely related to the growth of multilayer graphene by PUC on diamond [30]. Consequently, an extended PUC growth mechanism for GNW is proposed to interpret the growth GNWs on the diamond substrate that matches the experiment results very well.…”
Section: The Growth Mechanism Of Gnws Grown On Diamondsupporting
confidence: 65%
“…Mica samples are cleaved ex-situ and are loaded immediately into the UHV system. The UHV chamber (base pressure ∼ 6 × 10 −10 mbar) incorporates a solid carbon source that is made of glassy carbon, similar to that employed for p-doping in III-V MBE [16] and other carbon-related growth [17,18]. The dimensions of the carbon source are 10 × 2.5 × 0.3 mm 3 .…”
Section: Molecular Beam Growthmentioning
confidence: 99%
“…38 Growth of graphene on nickel surfaces has also been demonstrated based on diffusion and segregation of carbon from underlying amorphous carbon or nanodiamond films. 39,40 Conversely nickel films have been shown to transform the underlying carbon source to graphene at high temperature, forming bilayer graphene films directly on insulating substrates from polymers or self-assembled monolayers (SAMs) at low pressure conditions, 41 and few-layer graphene on The growth of uniform monolayer and bilayer graphene films has been achieved for CVD of methane at low pressures and high temperatures (1000 -1050 °C). Temperature is found to be an important factor for controlling graphene thickness, with thicker films (>5 layers) being produced at higher temperatures.…”
Section: Cobaltmentioning
confidence: 99%